Sustainable Education and Social Networks - Chaves-Montero, Alfonso (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Sustainable education and social networks are two important concepts that are closely related. The combination of sustainable education and social networks can be powerful in promoting positive change and creating a more sustainable future. Here are some ways in which these two concepts can be integrated:1. Online learning.2. Awareness raising.3. Collaboration.4. Engagement.5. Sharing of best practices.In conclusion, the integration of sustainable education and social networks has the potential to promote positive change and create a more sustainable future by making education more accessible, engaging, and impactful.